THE ROLE OF COMMUNITY COUNSELORS IN INCREASING CLIENTS SELF-CONTROL AT THE CORRECTIONAL CENTER CLASS I BANDAR LAMPUNG: THE ROLE OF COMMUNITY COUNSELORS IN INCREASING CLIENTS SELF-CONTROL AT THE CORRECTIONAL CENTER CLASS I BANDAR LAMPUNG - Ariyanti, Luh Yuke; Dona Raisa Monica; Muhammad Farid (Progressive Law Review, 2025)
The Correctional Center class I Bandar Lampung, hereinafter referred to as Bapas, plays an important role in providing guidance to juvenile and adult clients so that the clients can live well in society. Bapas itself has the main task and function of being a community supervisor who has the responsibility of guiding WBP (Correctional Prisoners) based on the rules and regulations of the institution that are still valid. The aim is to guide WBP to have awareness in order to make themselves better and not commit criminal acts that they have committed before or more severe criminal acts. The role of Community Counselors is carried out in the form of tasks and functions of community counseling in the stages of the criminal justice system for everyone who commits a crime, starting from the pre-sentencing and post-sentencing stages. During the pre-sentencing and sentencing process, Community Counselors are tasked with conducting community investigations and assisting ABH (Children in conflict with the law) as well as adult prisoners or adult clients.